2003
DOI: 10.1007/s00223-003-0064-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Vertebral Fractures on Lateral Chest Radiographs of Inner-City Postmenopausal Women

Abstract: We assessed the prevalence of vertebral fractures as a marker for osteoporosis on lateral chest radiographs in inner-city, minority, postmenopausal women. We reviewed outpatient lateral chest radiographs on all women 55 years and older at an inner-city hospital during two randomly selected months, August 2000 and April 2002. There were 106 women with a mean age of 65 (range 55-89) years, 45 were Hispanic, 42 Black, 9 White, 10 of other ethnicity. Deformity was graded on a 0-3 scale with Grades 2 (moderate) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
11

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 33 publications
2
22
0
11
Order By: Relevance
“…The prevalence rate of 24% for spine fractures found in this study is in the range compared to that found in previous studies involving Caucasian women of similar age groups (14-25%) [2,[12][13][14]. Of note, however, the presented prevalence of 24% included grade I fractures, and other studies also considering mild deformities revealed a higher prevalence of osteoporotic spine fractures (25-33%) [15][16][17].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The prevalence rate of 24% for spine fractures found in this study is in the range compared to that found in previous studies involving Caucasian women of similar age groups (14-25%) [2,[12][13][14]. Of note, however, the presented prevalence of 24% included grade I fractures, and other studies also considering mild deformities revealed a higher prevalence of osteoporotic spine fractures (25-33%) [15][16][17].…”
Section: Discussionsupporting
confidence: 54%
“…In a 60-year-old postmenopausal woman, this is the case for a BMD T-score of less than -4 without vertebral fractures, or if two or more insufficiency fractures are present, regardless the BMD. Unfortunately, several studies demonstrated that there is a poor reporting rate of vertebral fractures by radiologists [1,2,12,22]. In our study none of the osteoporotic deformities were mentioned in the official radiology report.…”
Section: Discussionmentioning
confidence: 58%
“…Objektyvios apžiūros metu maždaug trečdaliui (12 (36,4 proc.)) moterų buvo skausminga palpacija stuburo slankstelių projekcijoje bei nustatytas priestuburinių raumenų skausmas ir vietinis tonuso padidėjimas (9 (27,3 proc.)). Daugiau nei pusė tiriamųjų sirgo lėtinėmis širdies ir kraujagyslių ligomis 18 (54,5 proc.…”
Section: Rezultataiunclassified
“…Mūsų tyrime stuburo slankstelių lūžius patyrusių moterų grupėje taip pat nustatytas didesnis KMI vidurkis (27,42 kg/m 2 ), kuris klinikinėje praktikoje vertintinas kaip nutukimas. Nors kuo didesnis kūno masės indeksas, tuo didesnis kaulų mineralų tankis buvo konstatuotas, tačiau šių parametrų ryšys su slankstelių lūžių skaičiumi nenustatytas.…”
Section: Diskusijaunclassified
See 1 more Smart Citation